2023
DOI: 10.1002/jcb.30459
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effect of glabridin in ovalbumin induced allergic asthma and its comparison with methylprednisolone in a preclinical rodent model

Abstract: Glabridin, a polyphenolic flavonoid derived from Glycyrrhiza glabra (licorice) roots, has shown anti‐inflammatory and antioxidant properties. The current study sought to investigate glabridin's immunomodulatory effect in ovalbumin induced allergic asthma. Healthy male Wistar rats were divided into five groups. Group I served as a control group. Asthma was induced in groups II– IV. Groups III and IV were treated with glabridin (40 mg/kg) and methylprednisolone (15 mg/kg), respectively. Inflammatory cells counts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Additionally, l-SPD demonstrate sedative, anti-cholinergic, anti-allergic, and spasmolytic effects, suggesting potential applications in treating asthma, tremor paralysis, and other conditions. However, the lack of in vivo or in vitro experimental validation warrants further investigation.Research ndings indicate that Glabridin exhibits the ability to modulate the immune response by inhibiting proin ammatory cytokines, oxidative stress markers, IgE antibodies, and antioxidant enzymes, thereby proposing its potential as a novel therapeutic agent for the treatment of allergic asthma [32,33]. Licochalcone B has been demonstrated to inhibit the phosphorylation of serine 276 triggered by lipopolysaccharide (LPS) and the subsequent activation of NF-κB transcription, thereby alleciating oxidative stress, in ammation, and pathological changes in individuals with asthma [34].…”
Section: Potential Core Active Ingredientsmentioning
confidence: 99%
“…Additionally, l-SPD demonstrate sedative, anti-cholinergic, anti-allergic, and spasmolytic effects, suggesting potential applications in treating asthma, tremor paralysis, and other conditions. However, the lack of in vivo or in vitro experimental validation warrants further investigation.Research ndings indicate that Glabridin exhibits the ability to modulate the immune response by inhibiting proin ammatory cytokines, oxidative stress markers, IgE antibodies, and antioxidant enzymes, thereby proposing its potential as a novel therapeutic agent for the treatment of allergic asthma [32,33]. Licochalcone B has been demonstrated to inhibit the phosphorylation of serine 276 triggered by lipopolysaccharide (LPS) and the subsequent activation of NF-κB transcription, thereby alleciating oxidative stress, in ammation, and pathological changes in individuals with asthma [34].…”
Section: Potential Core Active Ingredientsmentioning
confidence: 99%
“…No side effects [263] Based on the findings from in vitro studies indicating the immunomodulatory activities of flavonoids, these polyphenolic compounds should also be considered as po-tentially effective preventive and therapeutic agents for asthma [251]. Indeed, several studies in OVA-induced asthmatic mice have shown that luteolin, hesperidin, glabridin, green tea catechins, and rosmarinic acid can significantly reduce both symptoms of bronchoconstriction and allergic airway inflammation level by decreasing the Th2 cytokine level, inflammatory cells infiltration, mucus secretion, interstitial fibrosis, and collagen deposition, accompanied by alleviation of airway hyperresponsiveness and lung function improvement [136,160,[278][279][280][281][282][283][284]. Recently, in a house dust mite (HDM)-induced asthma model, epigallocatechin gallate (EGCG), the major flavonoid extracted from green tea, has been demonstrated to decrease specific IgE in the serum while increasing IL-10 levels in the BALF, upregulate the amount of Treg cells and expression of Foxp3 mRNA in the lung tissue, thus effectively ameliorating tissue injury, airway inflammation and airway hyperresponsiveness [285,286].…”
Section: Asthmamentioning
confidence: 99%
“…Furthermore, polyphenols need to be investigated in terms of routes of administration, target tissues, adequate doses, as well as the most appropriate composition of phenolic extracts, as it appears that a combination of polyphenols may lead to a more effective beneficial effect. The potential use of polyphenols as preventive and therapeutic interventions requires preclinical studies testing a wide range of doses to determine the maximum safe single dose and the long-term safety profile polyphenols, owning to their natural origin, are essentially considered to be non-toxic and safe, which is further supported by data from preclinical and clinical studies reporting good tolerability of the evaluated phenolic compounds with the advantages of no adverse effects and high safety [169,220,[244][245][246][247]249,[253][254][255]274,275,[282][283][284][285][286][287][288][289]293,294]. However, the amount of data available in this area is limited, and additional research is needed to assess the overall toxicity, and content of toxic substances generated during the polyphenol extraction process or food processing.…”
Section: Limitations and Future Challengesmentioning
confidence: 99%